Heavy Metal Levels in Wild Edible Mushroom Samples from Nayagram Block of Midnapore District, West Bengal - Das, Nilanjana (Indian Forester, 2007)
Concentrations of heavy metals (Pb, Cd, Cu, Zn, Mn, Fe and Ni) were determined in the fruit bodies of ten edible mushrooms collected from two different areas (roadside and forest areas) of Nayagram Block of Midnapore District, West Bengal. The analyses were performed using Atomic Absorbtion Spectrophotometer. In the mushrooms, the highest metal concentrations were measured as 4.7, 0.84, 59.0, 135.0, 37.0, 1438.0 and 8.6 mg/kg (dry weight basis) for Pb, Cd, Cu, Zn, Mn, Fe and Ni in Coprinus micaceus, Coprinus micaceus, Lycoperdon pyriforme, Leucocoprinus cepaestipes, Canstharellus cibarius and Macrolepiota procera respectively. The results indicated that the levels of some detrimental heavy metals viz. cadmium and lead were high in some wild edible species viz. Coprinus micaceus, Coprinus comatus and Macrolepiota procera. Therefore, it is wise to restrict the consumption of these mushrooms collected from roadside area of the study region.